Exploring Speaking Anxiety Levels and Coping Strategies Among English Department Student - Mariyana, Viona; Burhayani, Burhayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study is to investigate the extent of speaking anxiety and the coping strategies employed by English Department students. As a result, the purpose of this research is to provide an in-depth understanding of the form of speaking anxiety among university students and to understand how they cope with the problem. It is anticipated that the findings would give educational institutions important information on how to create interventions and supporting programs that can assist students in overcoming speech anxiety and enhancing their academic performance and learning environment. This study has examined the relationship between speaking anxiety levels and coping strategies used by English majors. Based on the results of the research conducted, several main conclusions can be drawn. Keywords: Anxiety, Learning, Public Speaking